Tests and proofs : 13th International Conference, TAP 2019, held as part of the third World Congress on Formal Methods 2019, Porto, Portugal, October 9-11, 2019, Proceedings /: 13th International Conference, TAP 2019, held as part of the third World Congress on Formal Methods 2019, Porto, Portugal, October 9-11, 2019, Proceedings. (2019) - Unknown
No abstract available